Sunday

April 20, 2014

April 20, 2014

Posted by **bill** on Thursday, April 26, 2012 at 5:47pm.

x+y=6

2. y=x^2-2x+1

y-3=x

How would I go about solving these?

- math -
**Reiny**, Thursday, April 26, 2012 at 6:27pm!. from the 2nd : y = 6-x

sub into the 1st:

x^2 + (6-x)^2 = 20

x^2 + 36 - 12x + x^2 - 20 = 0

2x^2 - 12x + 16 = 0

x^2 - 6x + 8 = 0

(x-4)(x-2) = 0

x = 4 or x = 2

2. from the 2nd: y = x+3

sub into the 2nd

proceed as above....

let me know what you got

**Related Questions**

maths - Expand (1+2x)^20 - (1-2x)^20) in ascending powers of x up to the term in...

TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

algebra - here is a rational expression, 20+2x/5-x for what value of x is the ...

Math - 1. Solve (2x -3)< 14 2.Solve 3.2x + 20.8 > 52.0 -7.2x

Liberal Arts Math - factor the polynomial completely: 2xy-3y-40x+60 2xy-40x-3y+...

Math - How do i expand and simplify (2x+5) (3x-4) 6x-8x+15x-20 6x+7x-20 13x-20 ...

math - I will try it with x=20, y=15 From this, you can supply coefficients and ...

Math - Find the Slope, if it exist of the given pair (-17,-3) and (-20,-9) is it...

algebra - Can you help me to find the product of -4x^2 and x^3 + 2x^2 - 5x + 3...